2002
DOI: 10.1128/iai.70.8.4045-4052.2002
|View full text |Cite
|
Sign up to set email alerts
|

Rickettsia rickettsiiInfection of Cultured Human Endothelial Cells Induces Heme Oxygenase 1 Expression

Abstract: Existing evidence suggests that oxidative insults and antioxidant defense mechanisms play a critical role in the host cell response during infection of endothelial cells by Rickettsia rickettsii, the causative agent of Rocky Mountain spotted fever. Heme oxygenase (HO), a rate-limiting enzyme in the pathway for heme catabolism, protects against oxidant damage in a variety of stress situations. Here, we report on the expression of the inducible and constitutive HO isozymes, HO-1 and HO-2, during R. rickettsii in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 67 publications
3
43
0
1
Order By: Relevance
“…In addition, the kinetics and intensities of induced HO-1 mRNA expression activation during 24 h of infection were almost identical among these specialized endothelial cell types ( Fig. 4A and B) and quite similar to those reported earlier for infected HUVECs (22). All ECs had a peak of HO-1 mRNA expression, predominantly at 3 to 7 h pi, with the exception of HPAECs, where this response was delayed to 14 h. Intriguingly, HMECs and SVHCECs demonstrated the highest level of HO-1 mRNA expression of about 4.5-and 3.8-fold in comparison with uninfected control, whereas HPMECs were least responsive, with about 2.2-fold induction (Fig.…”
Section: R Rickettsii Infection Of Different Types Of Endothelial Cesupporting
confidence: 69%
See 2 more Smart Citations
“…In addition, the kinetics and intensities of induced HO-1 mRNA expression activation during 24 h of infection were almost identical among these specialized endothelial cell types ( Fig. 4A and B) and quite similar to those reported earlier for infected HUVECs (22). All ECs had a peak of HO-1 mRNA expression, predominantly at 3 to 7 h pi, with the exception of HPAECs, where this response was delayed to 14 h. Intriguingly, HMECs and SVHCECs demonstrated the highest level of HO-1 mRNA expression of about 4.5-and 3.8-fold in comparison with uninfected control, whereas HPMECs were least responsive, with about 2.2-fold induction (Fig.…”
Section: R Rickettsii Infection Of Different Types Of Endothelial Cesupporting
confidence: 69%
“…Equal amounts of RNA isolated from infected ECs and corresponding uninfected cells (controls) using TRI-reagent protocol were subjected to Northern blot analysis using radioactively labeled cDNA probes designed for specific detection of cyclooxygenase 2 (COX-2) (Cayman Chemical) and HO-1 transcripts (22,24). The differences in sample loading on different lanes were corrected by stripping of the signals and reprobing for the GAPDH (glyceraldehyde-3-phosphate dehydrogenase) housekeeping gene.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Infections by influenza virus, 61 encephalomyocarditis virus, 62 Listeria monocytogenes, 63 and Rickettsia rickettsii 64 all show significant up-regulation of HO-1, suggesting that this enzyme may participate in cellular responses to some intracellular pathogens. We have assessed the expression of HO-1 in our DMVEC system following infection with the KSHV-related rhesus rhadinovirus (RRV).…”
Section: Discussionmentioning
confidence: 99%
“…Prostaglandins and leukotrienes are generated from arachidonic acid by the cyclooxygenase (COX) enzymes, which are controlled by heme oxygenase (HO-1) [Haider et al, 2002;Rydkina et al, 2002]. In vitro and in vivo studies of rickettsial infection have shown that increased COX-2 expression in endothelial cells is related to increased prostaglandin secretion, which may explain some of the clinical manifestations of rickettsioses, such as pain, fever and inflammation.…”
Section: Endothelium and Pathophysiology Of Rickettsiosesmentioning
confidence: 99%